Effects Of horizontal gene transfer on bacteriophage infectivity - Bushra, Adiba Effat; Islam, Farzana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.